Leadership Skills of Female National Party Leaders in Mexico: Amalia García, Cecilia Romero and Beatriz Mojica - Gonzalez Rosas, Erika Lourdes; Góngora Cervantes, Vanessa (Revista Mexicana de Ciencias Políticas y Sociales, 2020)
This article presents an analysis of the leadership of female political leaders in order to identify the individual skills of three cases of female national party leaders in Mexico. Profound interviews were conducted with Amalia García (PRD), Beatriz Mojica (PRD) and Cecilia Romero (PAN) to use their discourse to make out their leadership skills following Cardona’s model. Results show similarities between these leaders regarding their initiative, teamwork, conflict resolution and time management, as well as the influence of the elections in their decision-making processes and resilience. Their leadership displays more similarities than differences between their skills. The analysis of the leadership capabilities of women who were national party leaders —spaces pre- dominantly dominated by men— is an issue that has not been approached much beyond legal, political and cultural factors that allow for or hinder the political participation of women.